Spatio-temporal distribution of water availability in Karnali-Mohana Basin, western Nepal: hydrological model development using multi-site calibration approach (Part-A) - Pandey, Vishnu Prasad; Dhaubanjar, Sanita; Bharati, Luna; Thapa, Bhesh Raj (Elsevier, 2020)
Study region: Karnali-Mohana (KarMo) river basin, Western Nepal.